Cell-Specific Transcriptional Responses to Heat Shock in the Mouse Utricle Epithelium - Sadler, Erica; Ryals, Matthew M.; May, Lindsey A.; Martin, Daniel; Welsh, Nora; Boger, Erich T.; Morell, Robert J.; Hertzano, Ronna; Cunningham, Lisa L. (Frontiers in Cellular Neuroscience, 2020)
Sensory epithelia of the inner ear contain mechanosensory hair cells and glia-like supporting cells, both of which are required for hearing and balance functions. Each of these cell types has unique responses to ototoxic and cytoprotective stimuli. Non-lethal heat stress in the mammalian utricle induces heat shock proteins (HSPs) and protects against ototoxic drug-induced hair cell death. Induction of HSPs in the utricle demonstrates cell-type specificity at the protein level, with HSP70 induction occurring primarily in supporting cells, while HSP32 (also known as heme oxygenase 1, HMOX1) is induced primarily in resident macrophages. Neither of these HSPs are robustly induced in hair cells, suggesting that hair cells may have little capacity for induction of stress-induced protective responses. To determine the transcriptional responses to heat shock of these different cell types, we performed cell-type-specific transcriptional profiling using the RiboTag method, which allows for immunoprecipitation of actively translating mRNAs from specific cell types. RNA-Seq differential gene expression analyses demonstrated that the RiboTag method identified known cell type-specific markers as well as new markers for hair cells and supporting cells. Gene expression differences suggest that hair cells and supporting cells exhibit differential transcriptional heat shock responses. The chaperonin family member Cct8 was significantly enriched only in heat-shocked hair cells, while Hspa1l (HSP70 family), and Hspb1 and Cryab (HSP27 and HSP20 families, respectively) were enriched only in supporting cells. Together our data indicate that hair cells exhibit a limited but unique heat shock response, and supporting cells exhibit a broader and more robust transcriptional response to protective heat stress.